Assessment of The Limitation of Potting Size on the Performance of Young Fig Plant in Greenhouse - Nur Amalina Zulkifli (School of Bioprocess Engineering, University Malaysia Perlis, 2019)
To estimate the amount of soil moisture lost from root zone during early growth on Fig in two different size pot. To compare the growth performance by shoot length, number of leaf, and surface area of leaf as limited by root zone size. To evaluate the amount of water loss for the fig plant based on pot size.